Effect of approach run velocity on the optimal performance of the triple jump - Liu, H.; Mao, D.; Yu, B. (Journal of Sport and Health Science, 2015)
Purpose: The purpose of this study was to determine the effect of horizontal and vertical velocities at the landing of the last step of approach run on the performance and optimal phase ratio of the triple jump. Methods: Three-dimensional kinematic data of 13 elite male triple jumpers were obtained during a competition. Computer simulations were performed using a biomechanical model of the triple jump to determine the longest actual distance using the optimal phase ratio with altered horizontal and vertical velocities at the landing of the last step of approach run. Results: The actual distance obtained using the optimal phase ratio significantly increased as the horizontal velocity at the landing of the last step of approach run increased (p=0.001) and the corresponding downward vertical velocity decreased (p=0.001). Increasing horizontal velocity at the landing of the last step of approach run decreased optimal hop percentage and increased optimal jump percentage (p=0.001), while decreasing corresponding downward vertical velocity increased optimal hop percentage and decreased optimal jump percentage (p=0.001). Conclusion: The effects of the velocities at the landing of the last step of approach run on the optimal phase ratio were generally small and did not qualitatively alter optimal techniques.